Hexavacant γ-Dawson-type phosphotungstates supporting an edge-sharing bis(square-pyramidal) {O2M(μ3-O)2(μ-OAc)MO2} core (M = Mn2+, Co2+, Ni2+, Cu2+, or Zn2+). Issue 21 (19th February 2019) - Suzuki, Kosuke; Minato, Takuo; Tominaga, Naoto; Okumo, Ichiro; Yonesato, Kentaro; Mizuno, Noritaka; Yamaguchi, Kazuya
Abstract : Reaction of hexavacant α-Dawson phosphotungstates with metal species in acetonitrile affords γ-Dawson structures supporting a bis(squarepyramidal) core. Abstract : In aqueous media, the introduction of additional metal species into polyoxometalates (POMs) with multiple vacant sites, such as a hexavacant Dawson-type phosphotungstate, which is of interest for the synthesis of novel metal oxide clusters, is generally difficult because they easily undergo self-condensation and/or structural decomposition. In this study, we succeeded in developing a novel synthetic method to obtain metal-substituted γ-Dawson-type phosphotungstate monomers by introducing metal species into an organic solvent-soluble lacunary phosphotungstate, TBA4 H10 [α-P2 W12 O48 ] (I ) (TBA = tetra- n -butylammonium), in organic media. The reaction ofI, which possessed two types of vacant sites, i.e. middle and edge sites, with divalent metal species such as Mn 2+, Co 2+, Ni 2+, Cu 2+, or Zn 2+ in acetonitrile afforded a series of isostructural POMsM2 (TBA5 [γ-P2 W12 O44 M2 (OAc)(CH3 CONH)2 ]· n H2 O· m CH3 CN; M = Mn 2+, Co 2+, Ni 2+, Cu 2+, or Zn 2+ ; OAc = acetate) with an edge-sharing bis(square-pyramidal) {O2 M(μ3 -O)2 (μ-OAc)MO2 } core. The bis(square-pyramidal) core was selectively placed at the middle site of the hexavacant lacunary phosphotungstate, and the two metals in the core were bridged by two phosphate units and one acetate species. Meanwhile, the edge sites were capped by acetimidate ligands, which protect the reactive lacunary POM from self-condensation. To the best of our knowledge, this is the first report describing the synthesis and characterization of metal-substituted hexavacant γ-Dawson-type POM monomers.